Managing the Documents of Adult Education– Historical Perspective - Bo Chang (Adult Education Research Conference, 2015)
In this paper, the author discussed how to collect and analyze data in historical perspective. In historical inquiry, researchers identify the research questions, specify the domain which relates to the research questions, and familiarize themselves with how the documents are structured and managed in the host library. In collecting data, researchers do not need to limit themselves to how the documents are labeled by the archivists. They can break the boundaries of the labeled documents and find out how seemingly unrelated documents are actually interrelated. Positivists and constructionists view history differently, which results in different approaches in how historical data can be analyzed. Positivists believe in transparent and universal truth generalized and/or inferred from the historical data. Constructionists regard that generalization and inference are not sufficient for researchers to understand why certain historical events occurred. Situating themselves in the historical context and/or establishing empathy enables researchers to feel the historical moments and explain and interpret data in the historical context. To better support historical study, the author provides suggestions to the data host libraries, the agents which provide the historical data, and conferences and journals which officially document the historical data.
Keywords: historical data; data collection; data analysis